1996
DOI: 10.1111/j.1365-2265.1996.tb02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose recombinant human growth hormone normalizes bone metabolism and cortical bone density and improves trabecular bone density in growth hormone deficient adults without causing adverse effects

Abstract: Our results suggest that 12 months of rhGH treatment at the lowest doses so far used normalizes bone metabolism and cortical bone density, and improves trabecular bone density without causing adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 60 publications
6
25
0
5
Order By: Relevance
“…Our findings are in line with the idea that a low GH dose seems optimal for restoring bone mass in GHD adults, as it avoids the initial decline in BMD frequently observed when higher doses are used (1,4,27,28). GH is a stimulator of both bone resorption and bone formation (29), and a low dose of GH may generate a more marked anabolic action than higher doses, as low IGF-I stimulates bone formation more markedly than bone resorption (30,31). Abrahamsen et al (28) have demonstrated that 0.004 mg/kg/day of GH stimulated bone remodeling and increased BMD over 12 months in GHD patients, irrespective of gender, while a higher dose of 0.015 mg/kg/day was associated with initial declines in forearm and whole-body BMD in their patients.…”
Section: Discussionsupporting
confidence: 75%
“…Our findings are in line with the idea that a low GH dose seems optimal for restoring bone mass in GHD adults, as it avoids the initial decline in BMD frequently observed when higher doses are used (1,4,27,28). GH is a stimulator of both bone resorption and bone formation (29), and a low dose of GH may generate a more marked anabolic action than higher doses, as low IGF-I stimulates bone formation more markedly than bone resorption (30,31). Abrahamsen et al (28) have demonstrated that 0.004 mg/kg/day of GH stimulated bone remodeling and increased BMD over 12 months in GHD patients, irrespective of gender, while a higher dose of 0.015 mg/kg/day was associated with initial declines in forearm and whole-body BMD in their patients.…”
Section: Discussionsupporting
confidence: 75%
“…Because of these evidences, the authors did not consider GHD as a condition of vitamin D deficiency [25]. Similar evidences of normal vitamin D levels have been found by other authors in studies performed in both childhood and adult-onset GHD [26][27][28].…”
Section: Impact Of Ghd On Vitamin D Levelssupporting
confidence: 63%
“…Serum 25OH-D3 and other markers of bone metabolism were evaluated before, after 12 months of therapy and after 12 months off, using a low weekly dose (70 pg/kg/week divided into 3 injections). Despite a significant improvement in IGF-I levels and in bone mineral density, no significant changes were found during the study in vitamin D and in other bone markers, indicating that GH acts on bone structure and its effects can be direct or mediated by IGF-I and not by vitamin D [28]. However, the low dose used and the frequency of GH administration must be taken into account in the interpretation of these results.…”
Section: Impact Of Gh Treatment On Vitamin D Levelsmentioning
confidence: 72%
“…This finding showed that a low dose of GH could increase IGF1 levels and have a pronounced physical effect in the GH-deficient adult (an increase in exercise capacity and in fat-free mass, and a decline in fat mass), without the side effects observed at higher dosage schedules. In the study by Amato et al (34), the lowest dose so far used in trials focusing on bone metabolism and structure in AGHD was used in a dosing regimen of 70 mg/kg per week divided into three injections. Results suggested that 12 months of lowdose GH therapy normalised bone metabolism and cortical bone density, and improved trabecular bone density without causing adverse events.…”
Section: Weight-based Vs Individualised Regimensmentioning
confidence: 99%
“…Regimens employing three injections per week have been shown to improve and/or normalise heart structure and performance, together with lipid profile, body composition, and bone metabolism and structure (23,34). In a randomised, prospective, controlled study comparing daily vs tiw injections (37), the tiw injection regimen was effective in normalising IGF1 levels and improving lipid profile, body composition, bone metabolism and bone density; this effect was comparable with that observed in patients treated with daily injections, with few side effects and good compliance.…”
Section: Timing and Frequency Of Gh Administrationmentioning
confidence: 99%